2012
DOI: 10.1007/s13197-012-0716-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brown rice flour fortification on the quality of wheat-based dough and flat bread

Abstract: The objective of present study was to investigate the impact of Brown Rice flour (BR) incorporation, at three different levels of 5, 10 and 15 % to the Wheat Flour (WF) preparations on rheological properties of wheat-based dough and quality of wheat-based flat bread. The BR flour incorporation mainly affected the chemical properties of flours, the rheological characteristics of dough and, quality and shelf life of bread. The protein-related properties of flours principally experienced reduction; however, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Khoshgozaran‐Abras et al . () also reported the ST was negatively affected by the fortification of brown rice flour. The higher stability values are always related to the strength of flours (Marco & Rosell, ), and it usually depends on the protein network (Martínez et al ., ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Khoshgozaran‐Abras et al . () also reported the ST was negatively affected by the fortification of brown rice flour. The higher stability values are always related to the strength of flours (Marco & Rosell, ), and it usually depends on the protein network (Martínez et al ., ).…”
Section: Resultsmentioning
confidence: 92%
“…Hydrophobic groups of amylose‐lipid complexes prevent starch to absorb moisture and hydrolyse (Hagenimana et al ., ). Therefore, more free water released to dough matrix by mixing and the ST of 50% EBRF decreased (Khoshgozaran‐Abras et al ., ). Lazaridou et al .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Breads are the most common baked products, usually produced from wheat refined flour. Bread was prepared from blends of BR flour with buckwheat flour sourdough (Capuani, Behr, Arendt, & Vogel, ) or BR flour with wheat flour (Khoshgozaran‐Abras, Azizi, Bagheripoor‐Fallah, & Khodamoradi, ). BR flour obtained after 24 hr of germination resulted in bread with improved texture (Cornejo & Rosell, ).…”
Section: Development Of Food Productsmentioning
confidence: 99%
“…This may be caused by the different nature of cereal materials. Khoshgozaran‐Abras, Azizi, Bagheripoor‐Fallah, and Khodamoradi () found that the lower DT was more suitable to get appropriate dough. Therefore, dough made with substituted ECF and UECF was desired.…”
Section: Resultsmentioning
confidence: 99%